Identifikasi Sifat Kimia Tanah pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq.) Rakyat yang Berbeda Umur Tanam di Desa Songga Kabupaten Landak - Sitanggang, Andreas; Indrawati, Uray Suci Yulies Vitri; Agustine, Leony (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2026)
Inceptisol is a type of soil that develops from igneous, sedimentary, and metamorphic parent materials. Inceptisol as a newly developed soil has a variety of textures, from coarse to fine, and depends on the level of weathering of its parent material. The problem of soil fertility in oil palm plantations of different planting ages is soil pH and low nutrient content, resulting in a lack of oil palm productivity. This study aims to determine the status of soil fertility and determine the recommended fertilizer dosage for oil palm plantations of different planting ages in Songga Village, Menyuke District, Landak Regency. This study was conducted on oil palm plantations owned by farmers in Songga Village, Menyuke District, Landak Regency. This study used a survey method. Observation points were determined based on 4 plots, each plot consisting of 15 points determined diagonally, from 15 observation points composited into 3 soil samples. Fertilization recommendations for each research location are at location A Urea 219.77 kg/Ha, SP-36 184.5 kg/Ha, and KCl 153.75 kg/Ha. Location B Urea 225.64 kg/Ha, SP-36 184.5 kg/Ha, and KCl 153.75 kg/Ha. Location C Urea 222.77 kg/Ha, SP-36 184.5 kg/Ha, and KCl 153.75 kg/Ha. Location D Urea 215.61 kg/Ha, SP-36 70.75 kg/Ha, and KCl 153.75 kg/Ha..